Identification and isolation of antimicrobial compounds from the flower extract of Hibiscus rosa-sinensis L: In silico and in vitro approaches. (October 2018) - Vijayakumar, S.; Morvin Yabesh, J.E.; Arulmozhi, P.; Praseetha, P.K.
Abstract: The modern people are preparing the natural medicines from the plants and their parts for curing various diseases. The present study was chosen Hibiscus rosa-sinensis flowers to analyze its antimicrobial capabilities against venereal diseases causing pathogens. In this study, the antimicrobial activity performed in different solvents prepared flower extracts using agar well diffusion method. Among the extracts, the methanolic flower extract of Hibiscus rosa-sinensis shows better results than other solvents extracts. The extract analysed by GC-MS which was exposes seven bioactive molecules. These bioactive molecules were docked with N. gonorrhoea protein. Finally, benzene dicarboxylic acid had best glide docking XP scores −7.955 with better binding energy values (−38.692 kcal/mol) than other ligand molecules. Hence, this molecule was isolated from the flowers of H. rosa-sinensis . After that, the different concentrations of 1, 2 benzene dicarboxylic acid were tested on human diseases causing microbial strains. There, all the levels were showed good anti-gonorrhoeal activity against N. gonorrhoeae. Hence this study suggested that 1, 2 benzene dicarboxylic acid could be used as a better drug candidate for venereal diseases. Highlights: The 1, 2 benzenedicarboxylic acid isolated from Hibiscus rosa-sinensis methanolic flowers extract in first time. Computational approach was applied to gain insight into selectivity for antimicrobial inhibitors. Structural elucidation was achieved by extensive analysis of spectroscopic data.